Susa mint: 311-301 BC - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2020)
This paper is the final component in a trilogy that documents a die study of the large denomination coinage issued from the Susa mint prior to 300 BC. It examines the Alexandrine coinage of Seleukos struck in the period 311/0-304/3BC, prior to the introduction of coinage bearing his own name. Three groups (Groups 5-7) are recognized in this coinage. Groups 5 and 6, bear a laurel wreath symbol, which in the case of Group 6 is accompanied by a range of other symbols. These two groups were struck simultaneously during the Babylonian War in the period c. 311/0-309/8 BC. Group 7 post-dates the Babylonian War. It is characterised by the presence of the anchor symbol, which displaced the laurel wreath as the primary symbol on the coinage. On the last reverse dies of Group 7 this anchor symbol was erased, a phenomenon previously identified on coinage from the mints of Babylon II and Uncertain Mint 6A (Opis), dated to c. 305/4-304/3 BC. This was a synchronous event across Seleukos’s mints operating in Babylonia and Susiana, one that provides a firm chronological peg for the last of the Susa issues (Group 7) in the name of Alexander, an updating of a decade relative to that proposed in Seleucid Coins.